Inflammatory stimuli induce shedding of heparan sulfate from arterial but not venous porcine endothelial cells leading to differential proinflammatory and procoagulant responses - Milusev, Anastasia; Despont, Alain; Shaw, Jane; Rieben, Robert; Sorvillo, Nicoletta (Scientific reports, 2023)
Endothelial dysfunction is an early event of vascular injury defined by a proinflammatory and procoagulant endothelial cell (EC) phenotype. Although endothelial glycocalyx disruption is associated with vascular damage, how various inflammatory stimuli affect the glycocalyx and whether arterial and venous cells respond differently is unknown. Using a 3D round-channel microfluidic system we investigated the endothelial glycocalyx, particularly heparan sulfate (HS), on porcine arterial and venous ECs. Heparan sulfate (HS)/glycocalyx expression was observed already under static conditions on venous ECs while it was flow-dependent on arterial cells. Furthermore, analysis of HS/glycocalyx response after stimulation with inflammatory cues revealed that venous, but not arterial ECs, are resistant to HS shedding. This finding was observed also on isolated porcine vessels. Persistence of HS on venous ECs prevented complement deposition and clot formation after stimulation with tumor necrosis factor α or lipopolysaccharide, whereas after xenogeneic activation no glycocalyx-mediated protection was observed. Contrarily, HS shedding on arterial cells, even without an inflammatory insult, was sufficient to induce a proinflammatory and procoagulant phenotype. Our data indicate that the dimorphic response of arterial and venous ECs is partially due to distinct HS/glycocalyx dynamics suggesting that arterial and venous thrombo-inflammatory disorders require targeted therapies.